GYF-21, an Epoxide 2-(2-Phenethyl)-Chromone Derivative, Suppresses Innate and Adaptive Immunity via Inhibiting STAT1/3 and NF-κB Signaling Pathways - Guo, Ran; Zhao, Yun-Fang; Li, Jun; Gu, Yu-Fan; Huo, Hui-Xia; Li, Shan-Shan; Song, Yue-Lin; Zhu, Zhi-Xiang; Tu, Peng-Fei (Frontiers in Pharmacology, 2017)
Multiple sclerosis is a chronic inflammatory autoimmune disease of the central nervous system characterized by demyelinating plaques and axonal loss. Inhibition on over activation of innate and adaptive immunity provides a rationale strategy for treatment of multiple sclerosis. In the present study, we investigated the inhibitory effects of GYF-21, an epoxide 2-(2-phenethyl)-chromone derivative isolated from Chinese agarwood, on innate and adaptive immunity for revealing its potential to treat multiple sclerosis. The results showed that GYF-21 markedly inhibited the activation of microglia, and dendritic cells as well as neutrophils, all of which play important roles in innate immunity. Furthermore, GYF-21 significantly suppressed adaptive immunity via inhibiting the differentiation of naive CD4+ T cells into T helper 1 (Th1) and T helper 17 (Th17) cells, and suppressing the activation, proliferation and IFN-γ secretion of CD8+ T cells. The mechanism study showed that GYF-21 evidently inhibited the activation of STAT1/3 and NF-κB signaling pathways in microglia. In conclusion, we demonstrated that GYF-21 can significantly inhibit innate and adaptive immunity via suppressing STAT1/3 and NF-κB signaling pathways, and has potential to be developed into therapeutic drug for multiple sclerosis.